2020
DOI: 10.1101/2020.11.20.20234013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevention of severe COVID-19 in the elderly by early high-titer plasma

Abstract: BackgroundTherapies to interrupt progression of early COVID-19 remain elusive. Among them, convalescent plasma in hospitalized patients was unsuccessful, perhaps because antibody should be administered earlier. We advanced plasma infusions to the first 72 hours of symptoms to arrest COVID-19 progression.MethodsA randomized, double-blind, placebo-controlled trial of convalescent plasma with high IgG titers against SARS-CoV2 in elderly subjects within 72 hours of mild COVID-19 symptoms. The primary endpoint was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 15 publications
(21 reference statements)
1
34
1
4
Order By: Relevance
“…In the ConPlas-19 RCT (26), in which 49% of the patients had positive SARS-CoV-2 IgG at enrollment, CCP did not confer benefit, but there was a trend towards reduced mortality. Nonetheless, in our study as in others (27, 66), antibody titers and symptom duration associated with disease severity and a lack of evidence of CCP efficacy. This underscores the longstanding principle that convalescent antibody therapy is most likely to be effective early in the course of viral respiratory diseases (14) as shown for COVID-19 in propensity score matched studies (23, 49) and a recently published outpatient RCT (66).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In the ConPlas-19 RCT (26), in which 49% of the patients had positive SARS-CoV-2 IgG at enrollment, CCP did not confer benefit, but there was a trend towards reduced mortality. Nonetheless, in our study as in others (27, 66), antibody titers and symptom duration associated with disease severity and a lack of evidence of CCP efficacy. This underscores the longstanding principle that convalescent antibody therapy is most likely to be effective early in the course of viral respiratory diseases (14) as shown for COVID-19 in propensity score matched studies (23, 49) and a recently published outpatient RCT (66).…”
Section: Discussioncontrasting
confidence: 66%
“…Although our data suggest possible effects of age, disease severity, and corticosteroid use on CCP efficacy, prospective, randomized, controlled trials are needed to establish CCP efficacy and the effect of these and other covariates. Antibody-based therapies, including CCP have now shown promise in outpatients with mild to moderate COVID-19 (66, 75). However, nearly a year into the pandemic, effective therapies for hospitalized patients are still urgently needed, particularly for those who are elderly and at high risk for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…One RCT evaluated convalescent plasma with high anti-SARS-CoV2 IgG titers in older patients within 72 hours of mild covid-19 symptoms. In the convalescent plasma arm, 16.2% (13/80) progressed to severe respiratory diseases (respiratory rate ≥30 or O 2 sat<93%) 186 compared with 31.2% (25/80), in a preplanned interim analysis. Early administration of high titer convalescent plasma may play a role in mild to moderate disease, but we need more data to • Seen in up to 80% after any critical illness and includes loss of muscle mass, neuromuscular weakness, fatigue, dyspnea, decreased exercise tolerance, joint contractures, and sexual dysfunction.…”
Section: Convalescent Plasmamentioning
confidence: 99%
“…Trials were slow to be mounted in the early days of the pandemic, and all trials so far published have been small and statistically inconclusive for mortality. Six of the seven trials now in the public domain (none from the US) showed non-significantly lower mortality in the treated arms, averaging about 50%, but significant clinical improvements in other parameters were noted in some of the trials (12). Much larger trials are now on the verge of reporting, and by the time this Viewpoint is published, we may not have to rely on observational data to draw conclusions, but as of now, the most informative data we have is from observational studies.…”
Section: A Balanced Perspective In the Midst Of A Pandemicmentioning
confidence: 99%